Bioremediation of polluted water bodies using algae and microbial consortia - S.M, Dr. Indumathi; Goswami, Dr. Tapas Kumar; Rajendran, Naveen Kumar; Awasthi, Kanchan; Gupta, Suhas; Ramu, Nyalam; Chitrambalam M, Dr. Thiru (International Journal of Aquatic Research and Environmental Studies, 2025)
Water scarcity is an inescapable dilemma resulting from the swift depletion of Earth's resources and adverse environmental effects. The primary objective of this study is to examine the removal efficacy of indigenous microalgae in conjunction with bacteria under diverse settings and to assess the patterns of algae development in actual wastewater. This study evaluates the viability of using actual textile effluent as an incubator for microalgal cultivation and wastewater remediation. Textile effluent comprises a mixture of diverse inorganic and organic molecules, predominantly including dyes and fertilizers. The microalgal-bacterial consortia demonstrated potential as an effective method for the biological remediation of waste textiles. This study employed fed-batch reactors to treat actual textile wastewater during a 24-hour cycle for one week. The experiment was executed in three distinct phases: single phase, two-phase, and connection, aimed at nutrient removal. The findings show that a microalgae-bacteria consortia achieves optimal removal efficiencies of 56.6% for nitrate (NO3-), 87.5% for phosphorus (PO4), and 92.6% for chemical oxygen demands (COD), with optimum concentrations of 13.9 mg/L of chlorophyll and 1.8 g/L for bacteria dry cell pounds, correspondingly. Optimal color removal was attained in a singular phase (exclusively algae), 42.6%. The findings demonstrated that this technology efficiently addresses actual textile effluent cost-efficiently and generates wood suitable for use as a biological fertilizer and in energy-effective initiatives.
Keywords: Bioremediation, Polluted water, Algae, Microbial consortia